To Comply or not to Comply: Evidence on Changes and Factors associated with the Changes in Compliance with the UK Code of Corporate Governance - Shabbir, Amama (Cranfield University School of Management, 2008)
In the UK, listed companies are required to comply or explain reasons for non-compliance with the UK code of corporate governance. In this paper, using detailed compliance data for a panel of FTSE 350 companies, I first investigate how firms change their compliance practices over time. I then investigate the factors associated with these changes. The period covered in this study, that is 2000 to 2003, was marked by a sharp decline in the UK stock market, followed by intensive merger/acquisition and restructuring activity. It therefore offered a particularly good context for studying how firms’ compliance practices change in response to changing business conditions. I find that firms tend to behave in an opportunistic manner so far as their compliance is concerned – becoming more compliant when their prior period stock market performance declines and less so with improvements in their operating performance. Moreover, I find that mergers and acquisitions (which may be viewed as a somewhat aggressive response to a business shock) tend to decrease compliance, whereas reorganizations/restructuring (a rather defensive response) tends to increase compliance. These findings provide a useful insight about the behaviour of the firms. After all, the code was a response to the corporate scandals of the late 1980s and early 1990s that shook investor confidence in the UK. In some ways it is not surprising then to find that companies tend to `ride the waves` becoming more compliant when the going gets tough, and less so as performance improves. Both for companies and their investors these findings have important implications. For companies, the message is clear – it is consistency in compliance that matters. For investors, to separate the sheep from goat in terms of their compliance, it is important to look at governance arrangements beyond a mere year or two.
Keywords: The Combined Code; corporate governance; compliance index; board structure; firm performance; mergers and acquisitions; reorganizations